2020
DOI: 10.20538/1682-0363-2019-4-266-272
|View full text |Cite
|
Sign up to set email alerts
|

A case of anti-NMDA-receptor encephalitis presenting as febrile catatonia

Abstract: We described a case of anti-NMDA-receptor encephalitis presenting as febrile catatonia in a 22-year-old patient with no somatic burden. We looked into the dynamics of the disease and treatment strategy. In the discussion, we provided analysis of the presented case, as well as issues related to research perspectives in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Together, these studies suggest that psychotic patients with ABs against NMDAR NR1 in serum only and without clinical signs of anti-NMDAR encephalitis could be treated with traditional medications. On the other hand, several attempts to prescribe immunotherapy in AB-positive purely psychotic patients were associated with good outcomes in a number of case reports or case series [97, 99, 100]. Moreover, small studies reported “dramatic improvement” in all but one of the patients following immunotherapy (even in patients who tested positive only for NMDAR NR1/NR2) [101, 102].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these studies suggest that psychotic patients with ABs against NMDAR NR1 in serum only and without clinical signs of anti-NMDAR encephalitis could be treated with traditional medications. On the other hand, several attempts to prescribe immunotherapy in AB-positive purely psychotic patients were associated with good outcomes in a number of case reports or case series [97, 99, 100]. Moreover, small studies reported “dramatic improvement” in all but one of the patients following immunotherapy (even in patients who tested positive only for NMDAR NR1/NR2) [101, 102].…”
Section: Discussionmentioning
confidence: 99%
“…This refers to the study of evoked potentials, 50 , 51 in particular, the study of facial expressions, 52 , 53 , 54 , 55 the study of oculomotor alterations in patients with schizophrenia spectrum disorders 56 and autoimmune disorders in newly emerging psychotic states. 56 , 57 , 58 , 59 In general, the task is to carry out a network analysis of the identified disorders. 60 , 61 , 62 …”
Section: Discussionmentioning
confidence: 99%
“…This refers to the study of evoked potentials, 50,51 in particular, the study of facial expressions, [52][53][54][55] the study of oculomotor alterations in patients with schizophrenia spectrum disorders 56 and autoimmune disorders in newly emerging psychotic states. [56][57][58][59] In general, the task is to carry out a network analysis of the identified disorders. [60][61][62] Thus, the research carried out at the present time preserves the tradition of an integrated clinical and social approach, on the basis of which organizational models of psychiatric services are proposed.…”
Section: Care System For Special Patient Groupsmentioning
confidence: 99%